Experimental study and two-dimensional modelling of the plasma dynamics of magnetically driven shock waves in a coaxial tube - Moreno, Cesar Hugo (2003)
Plasma shocks can be magnetically driven during high current discharges in low-pressure gases, induced by an external electric circuit. Radial currents between two coaxial electrodes can be accelerated to velocities of the order of 10 cmìs−1, thus being an effective method to transform potential energy in kinetic energy. A series of experiments were conducted using a low energy plasma focus device to measure the dynamics of plasma shocks in coaxial tubes. The radial position of the current sheath near the closed end of the electrodes was determined by means of a magnetic probe. The pinching time at the open end of the electrodes was measured using a Rogowski coil. Both, the movement and shaping of the plasma sheath were modelled by means of finite elements. The sheath was represented by coupled conical segments carrying current, mass, internal energy and momentum. The Lorentz force accelerates each element in its normal direction, which leads to the continuous reshaping of the sheath. The numerical results are compared against the experimental data showing good agreement.ìs−1, thus being an effective method to transform potential energy in kinetic energy. A series of experiments were conducted using a low energy plasma focus device to measure the dynamics of plasma shocks in coaxial tubes. The radial position of the current sheath near the closed end of the electrodes was determined by means of a magnetic probe. The pinching time at the open end of the electrodes was measured using a Rogowski coil. Both, the movement and shaping of the plasma sheath were modelled by means of finite elements. The sheath was represented by coupled conical segments carrying current, mass, internal energy and momentum. The Lorentz force accelerates each element in its normal direction, which leads to the continuous reshaping of the sheath. The numerical results are compared against the experimental data showing good agreement.